2015
DOI: 10.2217/mmt.14.31
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer and Vitamin D: An Update

Abstract: Exposure of the skin to solar ultraviolet (UV) radiation has both risks and benefits for human health. Absorption of UV-B radiation by DNA results in mutations that underlie the development of skin cancers, as is apparent from genetic studies showing high occurrence of UV signature mutations within these tumors. UV-B radiation is also absorbed by 7-dehydrocholesterol to initiate vitamin D synthesis. In experimental studies vitamin D metabolites enhance apoptosis of malignant cells, inhibit angiogenesis and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 109 publications
(108 reference statements)
0
17
0
Order By: Relevance
“…Also, a recent study did not find an effect of vitamin D supplementation on preventing falls and bone fractures in heathy adults (218). Some observational studies have reported a higher incidence of skin cancer with high vitamin D levels (219)(220)(221), but this is probably due to confounding from sun exposure, as shown in a recent Danish study (222).…”
Section: Vitamin D Deficiency In Organ Transplant Recipientsmentioning
confidence: 91%
“…Also, a recent study did not find an effect of vitamin D supplementation on preventing falls and bone fractures in heathy adults (218). Some observational studies have reported a higher incidence of skin cancer with high vitamin D levels (219)(220)(221), but this is probably due to confounding from sun exposure, as shown in a recent Danish study (222).…”
Section: Vitamin D Deficiency In Organ Transplant Recipientsmentioning
confidence: 91%
“…Additionally, nicotinamide or Vitamin B and Vitamin D is also widely used for prevention. The antiproliferative effects of 1,25(OH)D, or the biologically active form of Vitamin D, through epigenetic and modulation of clusterin 31 …”
Section: Nonsurgical Treatmentmentioning
confidence: 99%
“…There is clear evidence that sun exposure increases the risk of developing all types of skin cancer, although it is also essential for vitamin D synthesis [47]. UV radiation has been recognized as an important carcinogenic factor causing cancer of the skin or lips.…”
Section: Cancersmentioning
confidence: 99%
“…It is also important to maintain the 25(OH)D level at about 20 ng/mL or higher. In many places around the world this is achievable even with brief periods of midday sun exposure in most seasons [47]. However, the relationship between the level of exposure to solar radiation and the development of various types of neoplasms is complex and perhaps depends more on the nature and duration of exposure than on the average exposure to this radiation [48].…”
Section: Cancersmentioning
confidence: 99%